Analisis Supply Chain Beras Menggunakan Metode Food Supply Chain Network Di Desa Sebubus - Herlindi, Natia (Universitas Multi Data Palembang, 2024)
Farmers' income in Sebubus Village is uncertain every year, this phenomenon requires an analysis of the overall supply chain flow performance based on the problems that occur in Supply Chain Management (SCM) throughout Sebubus Village, namely the distribution flow of rice that is not optimal because there is only one rice factory in Sebubus Village. There are problems related to the uncertainty of the quantity of rice supply that hinders the production of the rice supply chain. Farmers are not satisfied with the profits they get because the rice must be sold directly to collectors. Because the weakness of the rice factory in Sebubus Village causes farmers not to make big profits. By applying the Food Supply Chain Network (FSCN) method, to understand the relationship between product flow, information flow, and financial flow throughout the series of rice cultivation activities. The main objective of this approach is to identify efficient workflows to accelerate supply chain management. The application of the food supply chain network concept is to determine the relationship between interconnected elements. The results of the study obtained were the total margin obtained by agents and wholesalers, which was Rp. 9000/Kg, the total cost incurred is Rp.2,500/Kg farmer share obtained is 40%. Marketing efficiency obtained is 16.6% is said to be efficient. So from the results of farmer share and marketing efficiency, the rice supply chain in Sebubus Village, Paloh District, Sambas Regency is efficient to carry out. Keywords—3-5keywords Rice, Sebubus Village, Food Supply Chain Network.